2019
DOI: 10.1159/000495611
|View full text |Cite
|
Sign up to set email alerts
|

Oral habits in Children with Cleft (Lip and) Palate: A Pilot Study

Abstract: Background/Aims: This pilot study aimed to evaluate the occurrence of oral habits and non-nutritive sucking habits in children with cleft (lip and) palate (CL/P) between 0–12 years, compared to peers without CL/P. Methods: Children with CL/P (mean age 6.0 years, SD 2.80) were recruited from the Ghent University Hospital and compared to gender- and age-matched children without CL/P (mean age 5.8 years, SD 3.09). A self-report questionnaire was developed and given to the caregivers. To compare the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 18 publications
(30 reference statements)
4
13
2
2
Order By: Relevance
“…Nevertheless, another pilot study reported an occurrence of thumb and finger sucking of 26.9% among children with cleft, however, this was not statistically significant when compared to children without cleft [26]. Thus, there was a higher percentage of finger sucking compared with our study.…”
Section: Discussioncontrasting
confidence: 93%
“…Nevertheless, another pilot study reported an occurrence of thumb and finger sucking of 26.9% among children with cleft, however, this was not statistically significant when compared to children without cleft [26]. Thus, there was a higher percentage of finger sucking compared with our study.…”
Section: Discussioncontrasting
confidence: 93%
“…), la respiración oral, la interposición lingual, etc. Los malos hábitos pueden alterar el normal desarrollo del sistema estomatognático produciendo un desequilibrio entre las fuerzas musculares externas e internas, ya que si una no ejerce su presión normal, permite que otra en su intensidad habitual produzca una deformación, dental u ósea (9) .…”
Section: Discusionunclassified
“…Existe un consenso en la literatura, que los hábitos de succión no nutritivos aumentan los factores de riesgo para maloclusiones esqueléticas, particularmente en la mordida abierta anterior (8)(9)(10)(11) . La causa presumible de mordida abierta anterior en niños con hábitos de succión es la inhibición del crecimiento vertical en la parte anterior del proceso alveolar, pero si el hábito cesa durante la fase de crecimiento, la posibilidad de corrección espontánea podría ser muy satisfactoria (12,13) .…”
Section: Discusionunclassified
“…The prevalence of oral habits in patients with cleft lip and palate is an area that has relatively been understudied among these patients and very few published reports have addressed this aspect of care in the literature (Barsi et al, 2013;Alighieri et al, 2019). Oral habits can significantly impact on the occlusion and oral health of patients with cleft lip and/or palate, thus further worsening their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, their study did not assess other important oral habits such as mouth breathing, bruxism, and snoring. A recent study, by Alighieri et al (2019) was carried out in Flemish Belgian children, aged 0 to 12 years. It assessed a fewer number of oral habits, including mouth breathing, snoring, and bruxism, which were not included in the first study by Barsi et al (2013).…”
Section: Introductionmentioning
confidence: 99%